2022
DOI: 10.3389/fphar.2022.996824
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ knowledge, attitude and practice towards National Centralized Drug Procurement policy in central China: A cross-sectional study

Abstract: Background: National Centralized Drug Procurement (NCDP), an ongoing government-led policy starting in 2019 in China, aimed at reducing drug costs. During the implementation of NCDP, healthcare professionals (HCPs) still have a certain degree of concern about the policy, which affects the clinical use of related drugs.Objective: This study aims to assess the level of knowledge, attitude and practice (KAP) of HCPs towards NCDP policy, together with the associated factors that determine their KAP.Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…support this policy. Compared to the previous understanding of the policy of centralized drug collection, dentists had a higher awareness of the policy of centralized implant collection [12].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…support this policy. Compared to the previous understanding of the policy of centralized drug collection, dentists had a higher awareness of the policy of centralized implant collection [12].…”
Section: Discussionmentioning
confidence: 78%
“…We used PASS 11.0 to calculate the sample size.There has been no previous research investigating the awareness rate of dentists regarding the policy of centralized dental implant procurement, so we referred to previous study reported that knowledge rate of doctors about drug centralized procurement policy which was 62.5% [12]. And we set α = 0.05, β = 0.1.…”
Section: Simple Sizementioning
confidence: 99%
“…At the same time, thanks to strong policy advocacy, patient recognition and trust regarding the bid-winning drugs continue to grow, despite the bias among some patients against generics prior to NCDP implementation. In public medical institutions, the incentive mechanism related to the agreed usage of the bid-winning drugs and the practice of supporting medical insurance policies have both increased clinicians' willingness to use bid-winning drugs (51). In the long run, the drug use structure of public medical institutions and the drug consumption habits of patients will further change, and the bid-winning enterprises will establish brand effects without spending money on advertising.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…In November 2018, 11 pilot cities for centralized drug procurement including Beijing and Tianjin were established, which was the "4 + 7" volume procurement that caused a stir in the industry [9] . [10]…”
Section: Concept Of Centralized Procurementmentioning
confidence: 99%